2015
DOI: 10.1111/1467-8500.12131
|View full text |Cite
|
Sign up to set email alerts
|

Residential Aged Care Policy in Australia – Are We Learning from Evidence?

Abstract: The residential aged care industry in Australia will expand rapidly over the next 10 years leading to substantial increases in government expenditure. Recent and future reforms are likely leading to changes in the structure of the industry with a potential impact on quality of care. The purpose of this paper is to stimulate broader public debate, based on the available evidence, about the preferred structure of this important industry. It examines the literature on the impact structure has on the quality of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…This paper complements previous studies that evaluate the efficiency of the Australian aged care system using a unique dataset. The analysis reported in this paper is drawn from unpublished data from private residential aged care facilities, which are operated by members of the Aged Care Guild (a group of large for‐profit providers).…”
Section: Resultsmentioning
confidence: 70%
“…This paper complements previous studies that evaluate the efficiency of the Australian aged care system using a unique dataset. The analysis reported in this paper is drawn from unpublished data from private residential aged care facilities, which are operated by members of the Aged Care Guild (a group of large for‐profit providers).…”
Section: Resultsmentioning
confidence: 70%
“…Previously Baldwin et al. (, p. 139) and Xu et al. () found that NFP providers delivered higher quality of care when compared with FP organisations, and the findings suggest that the underlying hidden ingredient may be the quality of carer support in place.…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps that is the reason why after an extensive review of predominantly international literature, Baldwin et al. (, p. 139) found that NFP providers delivered higher quality of care. Similarly, Xu, Kane, and Shamliyan () found that NFP organisations delivered better quality care compared with FPs in Canada and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…More routine and transparent data collection is essential for meaningful policy development (Baldwin et al. ). Within government, multi‐agency involvement will also assist in sharing data and learning from prior policy experience (Adams et al.…”
Section: Resultsmentioning
confidence: 99%